Independent and disparate evolution in nature of influenza A virus hemagglutinin and neuraminidase glycoproteins. - Kilbourne, E D (1990)
The hemagglutinin (HA) and neuraminidase (NA) external glycoprotein antigens of H1N1 and H3N2 subtypes of epidemiologically important influenza A viruses prevalent during recent decades were subjected to intensive antigenic analysis by four different methods. Prior to serological analysis with polyclonal rabbit antisera, HA and NA antigens of four viruses of each subtype were segregated by genetic reassortment to forestall nonspecific steric hindrance during antigen-antibody combination. This analysis has demonstrated that with respect to antigenic phenotype, HA and NA proteins have evolved at different rates. With H1N1 viruses, an arrest of significant evolution of the NA discordant with the continuing antigenic drift of HA was found in the 1980-1983 period. It is probable that the different and independent rates of evolution of HA and NA reflect the greater selective pressure of HA antibodies, which forces the more rapid emergence of HA escape mutants. The slower antigenic change found for NA further supports the potential for NA-specific infection-permissive immunization as a useful stratagem against influenza.